Catalytic Reduction of Aromatic Nitro Compounds to Phenylhydroxylamine and Its Derivatives - Min Yu; Dachen Ouyang; Liqiang Wang; You-Nian Liu (Molecules)
Phenylhydroxylamine and its derivates (PHAs) are important chemical intermediates. Phenylhydroxylamines are mainly produced via the catalytic reduction of aromatic nitro compounds. However, this catalytic reduction method prefers to generate thermodynamically stable aromatic amine. Thus, designing suitable catalytic systems, especially catalysts to selectively convert aromatic nitro compounds to PHAs, has received increasing attention but remains challenging. In this review, we initially provide a brief overview of the various strategies employed for the synthesis of PHAs, focusing on reducing aromatic nitro compounds. Subsequently, an in-depth analysis is presented on the catalytic reduction process, encompassing discussions on catalysts, reductants, hydrogen sources, and a comprehensive assessment of the merits and drawbacks of various catalytic systems. Furthermore, a concise overview is provided regarding the progress made in comprehending the mechanisms involved in this process of catalytic reduction of aromatic nitro compounds. Finally, the main challenges and prospects in PHAs’ production via catalytic reduction are outlined.